Constitutive model for stress–Strain responses of municipal solid waste considering fibrous reinforcement - Li, Xiulei; Peng, Bo; Li, Jinfeng (Frontiers in Earth Science, 2023)
The triaxial test results of municipal solid waste (MSW) with different fibrous content show that reinforcement of fibrous materials is the key factor affecting the mechanical properties of MSW. Thus, MSW is regarded as a composite of fibrous materials (plastic +textiles) and paste (i.e. Any other non-fibrous materials). Under load, its mechanical behavior is determined by the two materials listed above. This study introduces the notion of fibrous reinforced parameters and provides the corresponding evaluation equation. A new plastic potential function reflecting the reinforcement effect of fibrous materials is developed to establish the elastoplastic constitutive model for predicting stress-strain responses of MSW. Comparing anticipated and experimental findings of various MSW demonstrates that the suggested constitutive model's predictions are in good accord with the test data. This model reproduces the essential aspects of the upward curving of stress-strain curves and continuous volumetric strain increase with axial strain more precisely during loading, particularly for the upward curve form at a higher strain level. Meanwhile, the model is also able to capture the characterization of larger volumetric strains for MSW specimens with higher fibrous content and larger volumetric strain for lower confining stress. Comparing the measured data and model parameter analysis reveals that the suggested model can accurately mimic the mechanical and deformation properties of MSW, hence providing a theoretical foundation for the landfill project.